Potential role of Albizia lebbeck and Emblica officinalis on smooth muscle contractions in experimental animal models - R. Bansilal Tiwari; Mohammed Naseeruddin Inamdar; Raha Orfali; Syed Mohammed Basheeruddin Asdaq; Mamdouh Allahyani; Abdulelah Aljuaid; Abdulaziz Alsharif; Mehnaz Kamal; Ahad Amer Alsaiari; Mazen Almehmadi; Mohd Imran; Sultan Alshehri; et al. (Journal of King Saud University: Science, 2023)
Background and objective: Spasms are involuntary muscular contractions commonly seen frequently. This study used isolated tissue preparations to test the efficacy of Albizia lebbeck (A.L) and Emblica officinalis (E.O) extracts for spasmolytic activity. Materials and methods: The herbal extracts were tested in isolated guinea pig ileum, rat uterus, rat fundus, and rabbit jejunum. Histamine was used as spasmogen in guinea pig ileum, while 5-hydroxytryptamine (5-HT) was in rat uterus and rat fundus. Spontaneous contractions' amplitude and frequency were recorded in the rabbit jejunum after administering herbal extracts. The influence of the extracts on smooth muscle contraction was calculated and statistically analyzed by one-way ANOVA. The P value was kept at <0.05 for all statistical analyses to consider it significant. Results: Observation from the present study indicated that A.L significantly (p < 0.05) enhanced the contraction induced by histamine and 5-HT in guinea pig ileum (50 mcg/ml) and rat fundus (150 mcg/ml), respectively. In the rabbit jejunum, the amplitude and frequency of contraction were significantly (p < 0.05) reduced at 500 mcg/ml. E.O. was found to suppress the spasmogenic (histamine and 5-HT) at doses beyond 150 mcg/ml and, in rabbit jejunum, enhanced the amplitude and frequency of contraction at 50 and 150 mcg/ml. The IC50 values for E.O. in guinea pig ileum, rat uterus, and rat fundus were 35.2, 50.3, and 124.7 mcg/ml, respectively. Conclusion: The observation suggests that A.L enhanced smooth muscle contraction in the presence of known spasmogens and reduced it in the absence. Opposite effects were found for E.O., where it reduced contraction in the presence of spasmogens and increased in the absence. These findings suggest potential spasmogenic/spasmolytic activities of the tested extracts.